Peace and Governance in Africa - Fashagba, PhD, Joseph Olayinka; Oshewolo, Segun (Covenant University Journal of Politics and International Affairs, 2016)
While some are of the opinion that good governance thrives best in an atmosphere of peace, others overwhelmingly emphasise the natural peace-inducing potentials of good governance. From the latter brand of scholarship, good governance is a necessary requirement for sustainable peace. Unfortunately, the problems confronting Africa in this century are predominantly governance-related. African countries are poorly ranked on the global scale of governance indicators. The consequences of this include recurrent civil wars, genocides, and the proliferation of organised rebellions against the state. These have largely turned the continent into a region characterised by political instability. Thus, this paper examines the nexus between good governance and peace, focusing on Africa. In view of the enormous challenges that insecurity and crises have created in Africa, the paper recommends that African leaders must deepen democracy on a continental scale, demonstrate the willingness to combat and reduce corruption, build a strong civil society and consciously promote human rights and justice.